KARAKTERISTIK SIFAT KUALITATIF INDUK MURAI BATU (Copsychus malabaricus) SIAP PRODUKSI - Edo Mustaqim; Tintin Kurtini; Rr. Riyanti (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This research is aimed to identify and describe the characteristics of the qualitative nature of the parents white rumped shama which are ready for production includes, the coat color, body shape, eye shape, color of the oral cavity, shape of the head, neck shape, and the ability to sing. This research was conducted in the captivity white rumped shama in March 2016 in Metro, Bandar Jaya, and Bandar Lampung. The object being observed are 30 pairs of parents white rumped shama who ready for production in the range of 1.5 to 5.0 years of age. The data characteristics qualitative nature white rumped shama obtained by direct observation and record observations in the visual table of observations that have been provided. The data were analyzed by using the chi-square (X2) with a level of 5%. The research results shows that the characteristics of the qualitative nature the parents white rumped shama are the coat color, color of the oral cavity, and the ability to sing showed significant differences (P <0.05) on production readiness, while the body shape, eye shape, shape of head, and neck shape shows results not significant different (P> 0.05). Keywords: White Rumped Shama, Characteristic of Qualitative Nature, Production Readiness